Optimizing Nutrient Removal in Agriculture Wastewater Using Electrocoagulation Technology - Oktiawan, Wiharyanto; Sarminingsih, Anik; Hadiwidodo, Mochtar; Purwono, Purwono (Universitas Diponegoro, 2025)
Water pollution exacerbates global water crises by reducing freshwater availability and quality. Agricultural wastewater, containing pesticides, herbicides, fertilizers, and organic matter, can contaminate water bodies if untreated. This study optimizes electrocoagulation (EC) parameters—voltage, time, and calcium concentration—to maximize nitrogen compound removal using response surface methodology (RSM). Results show a nitrate reduction of 88.37% (2.960 mg/L) at 45 V, 15 minutes, and 7 mg/L calcium, while ammonia was reduced by 99.37% (0.016 mg/L) at 30 V, 1.5 minutes, and 4.5 mg/L calcium. Calcium enhances coagulation by forming calcium hydroxide. The optimal conditions for nitrate and ammonia removal (3.709 mg/L and 1.338 mg/L) were 45 V, 15 minutes, and 5.09 mg/L calcium. EC also removed 96.73% of iron, with magnesium concentrations remaining very low (0.001 mg/L).